PERSONAL SELLING STRATEGY ANALYSIS ON FUNDING PRODUCTS IN AN EFFORT TO INCREASE THE NUMBER OF CUSTOMER - Muhammad Anwar; Muhammad Ersya Faraby (I-Finance Journal, 2024)
This research aims to analyze and explain Personal Selling strategies for funding products at PT. BPR Syari'ah Sarana Prima Mandiri KCP Bangkalan in an effort to increase the number of customers. This research uses a qualitative descriptive method. The data analysis process uses data reduction techniques, data presentation and drawing conclusions. The research results show that PT. BPR Syari'ah Sarana Prima Mandiri KCP Bangkalan has carried out all stages of personal selling starting from Prospecting, Pre-approach, Presentation and Demonstration, Overcoming, Objection, Closing to Follow Up. The strategies implemented in an effort to increase the number of customers as follows: 1) Implementing a Savings Festival, 2) Implementing a personal selling strategy system 3) Taking advantage of opportunities, 4) Good service, attractive facilities and easy transactions, 5) Quick response to customer complaints. The conclusion is that efforts to increase the number of customers can be done using a personal selling strategy. This strategy includes comprehensive product marketing, with a focus on personal relationships, comfort, and consistent follow-up. Implementing this strategy will have a positive impact on the financial sustainability of PT. BPR Syari'ah Sarana Prima Mandiri KCP Bangkalan.